Influence of different thermoplastic polymer/wood powder ratios on mechanical and thermal properties of composite materials - Bessa, João (2017)
This work compares the influence of different thermoplastic polymer/wood powder ratios on mechanical and thermal properties of composite materials. Moreover, the effect of a coupling agent incorporation, to promote the adhesion between both components, on these properties was evaluated. The composite materials were obtained by compression moulding process and the mechanical and thermal tests were subsequently performed.